Research Progress on Neural Processing of Hand and Forearm Tactile Sensation: A Review Based on fMRI Research - Chen H; Fu S; Zhi X; Wang Y; Liu F; Li Y; Ren F; Zhang J; Ren L; Wang Y (Neuropsychiatric Disease and Treatment)
Hao Chen,1,* Shifang Fu,2,* Xiaoyu Zhi,2 Yu Wang,2 Fanqi Liu,2 Yuetong Li,2 Fengjiao Ren,2 Junfeng Zhang,1,3,4 Longsheng Ren,1 Yanguo Wang2 1Graduate School, Tianjin University of Traditional Chinese Medicine, Tianjin, 301617, People’s Republic of China; 2Rehabilitation Department, Tianjin University of Traditional Chinese Medicine Second Affiliated Hospital, Tianjin, 300250, People’s Republic of China; 3Rehabilitation Center, First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, 300193, People’s Republic of China; 4National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin, 300381, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanguo Wang, Tianjin University of Traditional Chinese Medicine Second Affiliated Hospital, Tianjin, 300250, People’s Republic of China, Email tjwangyanguo@163.comAbstract: Tactile perception is one of the important ways through which humans interact with the external environment. Similar to the neural processing in visual and auditory systems, the neural processing of tactile information is a complex procedure that transforms this information into sensory signals. Neuroimaging techniques, such as functional Magnetic Resonance Imaging (fMRI), provide compelling evidence indicating that different types of tactile signals undergo independent or collective processing within multiple brain regions. This review focuses on fMRI studies employing both task-based (block design or event-related design) and resting-state paradigms. These studies use general linear models (GLM) to identify brain regions activated during touch processing, or employ functional connectivity(FC) analysis to examine interactions between brain regions, thereby exploring the neural mechanisms underlying the central nervous system’s processing of various aspects of tactile sensation, including discriminative touch and affective touch. The discussion extends to exploring changes in tactile processing patterns observed in certain disease states. Recognizing the analogy between pain and touch processing patterns, we conclude by summarizing the interaction between touch and pain. Currently, fMRI-based studies have made significant progress in the field of tactile neural processing. These studies not only deepen our understanding of tactile perception but also provide new perspectives for future neuroscience studies.Keywords: neural processing mechanism, tactile perception, functional magnetic resonance imaging, review